Pelatihan Peningkatan Kompetensi Guru Mata Pelajaran IPS SMA dalam Penggunaan Internet Berbasis Metode E-Learning Kecamatan Tualang Kabupaten Siak - Sakdanur Nas; Isjoni Isjoni; M. Yogi Isjoni; Indra Primahardani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
In this case in accordance with the times that face the era of the industrial revolution 4.0 where the learning process no longer depends on guidebooks, but everything can be known by accessing internet media. In the conditions of the Covid 19 Pandemic, teacher learning processes can use internet-based e-learning methods. E-learning is a learning method that utilizes web-based information technology (IT) that can be accessed remotely so that learning is not only glued in the classroom and in certain hours but can still be done anytime and anywhere. Tualang District of Siak Regency has 4 SMAN spread in Tualang District of Siak Regency. Based on the results of observations, State High School Teachers in Tualang District of Siak Regency still do not use the Internet to the maximum in the learning process. Teachers use limited media and learning resources. This is due to lack of information and lack of facilitation in the development of teacher competence in the use of E-Learning-based internet. Based on these conditions, the use of internet based E-Learning is still not optimal. Devotional activities are held on September 1-4, 2021. This devotional activity is carried out with three stages, namely the preparation stage, the implementation stage and the final stage. With this devotional activity, it is expected that State High School teachers in Tualang District of Siak Regency can improve teacher competence in the use of E-Learning-based Internet, especially Google Classroom, Google Meet and Zoom Meeting So that the teacher can use it well in the learning process.